Analysis of The Flow of Funds of Money Laundering Crime With Predicate Crime of Narcotics Crime by Foreign Nationals, A Case Study at the National Narcotics Agency of Bali Province - Agung Darma Wibawa, Anak; Sihotang, Erikson; Nyoman Suandika, I (International Journal Labs, 2024)
The flow of funds of foreign nationals at home and abroad can be used in proving money laundering crimes in Indonesia because based on Article 69 of Law Number 8 of 2010 concerning Prevention and Eradication of Money Laundering Crimes, which states that in order to be able to carry out investigations, prosecutions, and examinations in court against money laundering crimes, it is not mandatory to prove the original criminal act first, with this intention it does not mean that in conducting investigations, prosecutions, and examinations in court it is not mandatory to prove the original criminal act. This study aims to determine and analyze the analysis of the flow of funds of money laundering crime with predicate crime of narcotics crime by foreign nationals. This research method uses normative research supported by empirical research using various types of primary legal materials. The results show that the flow of funds of foreign nationals at home and abroad can be used in proving money laundering crimes in Indonesia because based on Article 69 of Law Number 8 of 2010 concerning Prevention and Eradication of Money Laundering Crimes, which states that in order to be able to carry out investigations, prosecutions, and examinations in court against money laundering crimes, it is not mandatory to prove the original criminal act first. This research has implications for the importance of strengthening international cooperation in tracing and tracking the flow of funds involving foreign nationals, as well as the need to strengthen regulations related to the supervision of cross-border financial transactions.